Diagnostic delays among COVID‐19 patients with a second concurrent diagnosis. Issue 4 (13th February 2023) - Freund, Ophir; Azolai, Lee; Sror, Neta; Zeeman, Idan; Kozlovsky, Tom; Greenberg, Sharon A.; Epstein Weiss, Tali; Bornstein, Gil; Tchebiner, Joseph Zvi; Frydman, Shir
Abstract: Background: Little is known about the effect of a new pandemic on diagnostic errors. Objective: We aimed to identify delayed second diagnoses among patients presenting to the emergency department (ED) with COVID‐19. Designs: An observational cohort Study. Settings and Participants: Consecutive hospitalized adult patients presenting to the ED of a tertiary referral center with COVID‐19 during the Delta and Omicron variant surges. Included patients had evidence of a second diagnosis during their ED stay. Main Outcome and Measures: The primary outcome was delayed diagnosis (without documentation or treatment in the ED). Contributing factors were assessed using two logistic regression models. Results: Among 1249 hospitalized COVID‐19 patients, 216 (17%) had evidence of a second diagnosis in the ED. The second diagnosis of 73 patients (34%) was delayed, with a mean (SD) delay of 1.5 (0.8) days. Medical treatment was deferred in 63 patients (86%) and interventional therapy in 26 (36%). The probability of an ED diagnosis was the lowest for Infection‐related diagnoses (56%) and highest for surgical‐related diagnoses (89%). Evidence for the second diagnosis by physical examination (adjusted odds ratios [AOR] 2.35, 95% confidence interval [CI] 1.20–4.68) or by imaging (AOR 2.10, 95% CI 1.16–3.79) were predictors for ED diagnosis. Low oxygen saturation (AOR 0.38, 95% CI 0.18–0.79) and cough or dyspnea (AOR 0.48, 95% CI 0.25–0.94) in the ED were predictors of a delayed second diagnosis. Abstract :